1990
DOI: 10.1161/01.hyp.15.6.666
|View full text |Cite
|
Sign up to set email alerts
|

1989 Corcoran lecture: adaptive and maladaptive responses of the arterial wall to hypertension.

Abstract: This study reviews recent experimental data from our own and other laboratories on the effects of hypertension on the arterial wall and the potential mechanisms by which hypertension can induce vascular injury and accelerate atherosclerosis. The findings suggest that the responses of the arterial media to hypertension reflect appropriate adaptations to increased intramural tension with resultant medial thickening secondary to an increase in both cellular mass and extracellular matrix. The role of growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
2
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(55 citation statements)
references
References 50 publications
1
51
2
1
Order By: Relevance
“…It was reported that intimal thickening of large vessels develops with aging in male SHR due to increased deposition of extracellular matrix and increased migration of mononuclear cells (25). This is compatible with the histological changes of the carotid artery seen in our female obese SHR.…”
Section: Resultssupporting
confidence: 91%
“…It was reported that intimal thickening of large vessels develops with aging in male SHR due to increased deposition of extracellular matrix and increased migration of mononuclear cells (25). This is compatible with the histological changes of the carotid artery seen in our female obese SHR.…”
Section: Resultssupporting
confidence: 91%
“…However, the very large difference found suggests that increased transcription is the main factor in the greater concentration of mRNA found, although differences in stability may also contribute in part. The present study demonstrates greater abundance of transcripts for prepro-ET-1, but in our previous study 11 and other investigations of the vascular changes in DOCA-salt hypertension as well as in other models of hypertension, 17 it has been clearly demonstrated that a hypertrophic response occurs in the blood vessel wall. This hypertrophy affects to a certain degree the endothelium 17 as well as smooth muscle cells and other components of the blood vessel wall.…”
Section: Discussioncontrasting
confidence: 48%
“…Changes to the geometric configuration of vessels may lead to smooth muscle cell hypertrophy and increased collagen. The intimal layer of these stiffened vessels then becomes vulnerable to atherosis and to increased lipoprotein, albumin, and leukocyte permeability (28,29). Thus, an early effect of SLE on vascular stiffening may set the stage for an acceleration of the atherosclerotic process through traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%